The Structure of Classical Value Theories - May, Kenneth (Review of Economic Studies, 1949)
Journal Article The Structure of Classical Value Theories Get access Kenneth May Kenneth May Northfield, Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 1, 1949, Pages 60–69, https://doi.org/10.2307/2295789 Published: 01 April 1949